The effect of tamarind (Tamarindus indica) and lime (Citrus medica) juice washing on the sensory attributes and the rancidity development in breaded tilapia - A preliminary study - Bakar, Jamilah; Hamzah, Siti Aini (Universiti Putra Malaysia Press, 1997)
The feasibility of removing the muddy flavour and odour of black tilapia (Oreochromis mossambicus) with natural acid extracts from tamarind and lime by washing treatment (1.5% w/v tamarind juice, 1.5% v/v lime juice and a mixture of lime juice 0.75% and tamarind juice 0.75% was investigated. The effect of the washing treatment on rancidity development in breaded tilapia kept at -20°C was also monitored. Acid washing improved the acceptability for flavour and odour as detected by sensory panellists. Samples treated with tamarind juice were different from other samples and were scored significantly higher for flavour, odour and colour than other treatments. All treated samples had a significantly tougher texture than the control. However, the rancidity development as indicated l7y the percentage of thiobarbituric acid reactive substances (TBARS) values in stored samples was not retarded.